Nanostructures for oral medicine - Andronescu, Ecaterina; Grumezescu, Alexandru Mihai (Amsterdam Elsevier, 2017)
Nanostructures for Oral Medicine presents an up-to-date examination of the applications and effects of nanostructured materials in oral medicine, with each chapter addressing recent developments, specific applications, and uses of nanostructures in the oral administration of therapeutic agents in dentistry. The book also includes coverage of the biocompatibility of nanobiomaterials and their remarkable potential in improving human health and in reducing environmental pollution. Emerging advances, such as Dr. Franklin Tay's concept of a new nanotechnology process of growing extremely small, mineral-rich crystals and guiding them into the demineralized gaps between collagen fibers to prevent the aging and degradation of resin-dentin bonding is also discussed. This work will be of great value to those who work in oral medicine, providing them with a resource to gain a greater understanding of how nanotechnology can help them create more efficient, cost-effective products. In addition, it will be of great interest to those who work in materials science who wish to gain a greater appreciation of how nanostructured materials are applied in this field.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Nanomedicine; Nanostructured materials -- Therapeutic use; Oral medicine; Electronic books